Synthesis and characterization of layered metal sulfates containing MII3(μ3-OH/F)2(M = Mg, Co) diamond chains. Issue 4 (3rd January 2017) - Marri, Subba R.; Mahana, Sudipta; Topwal, Dinesh; Behera, J. N.
Abstract : Two-dimensional cobalt(ii ) and magnesium(ii ) sulfates with diamond chains comprising M3 (μ3 -F/OH)2 units have been synthesized and characterized. Abstract : Cobalt and magnesium sulfates of the compositions, [C4 N2 H12 ]2 [Co3 F2 (SO4 )3 (H2 O)2 ], (1 ) and [NH4 ]2 [Mg3 (OH)2 (SO4 )3 (H2 O)2 ], (2 ), respectively, have been synthesized under hydro/solvothermal conditions, and are characterized by IR spectra, elemental analysis, powder X-ray diffraction (PXRD), energy-dispersive X-ray spectroscopy (EDX), thermogravimetric analysis (TGA), and X-ray single-crystal diffraction.1 and2 crystallized in the orthorhombic space groups Pnma and Cmc 2 respectively. While1 is templated by the organic piperazinium cation, 2 is obtained in the presence of ammonium ions. The layered structures are formed by the diamond chains comprising of M3 (μ3 -OH/F)2 units (M = Co:1, Mg:2 ). Magnetic studies of1 reveal its ferromagnetic nature with a transition at 10.8 K and show it does not exhibit spin-glass freezing. Isothermal magnetization shows a hysteresis loop at 2.5 K with a coercive field of 1200 Oe and remnant magnetization of 0.1 μ B . A sharp λ-like anomaly is also seen in the heat capacity curve, favoring long range magnetic ordering below T c .